2008
DOI: 10.1016/j.ijrobp.2007.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Natural History, and Patterns of Locoregional Recurrence in Gastric Cancer Patients Treated With Preoperative Chemoradiotherapy

Abstract: Purpose-To retrospectively determine the incidence and patterns (in-field, marginal, or out-offield) of locoregional recurrence of gastric cancer in patients who received preoperative chemoradiotherapy and to determine the outcome in these patients. 1994 and 2004, 149 patients with gastric carcinoma were treated on institutional protocols with preoperative chemoradiation. Ultimately, 105 patients had an R0 resection. Sixty-five of these patients received preoperative chemotherapy followed by chemoradiotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
(25 reference statements)
2
14
0
Order By: Relevance
“…However, the prognostic value of a pathologic complete response after neoadjuvant treatment for gastric cancer is still a matter of debate 39 and deserves further analyses. Unfortunately, the magic trial has not reported a rate of complete pathologic response.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prognostic value of a pathologic complete response after neoadjuvant treatment for gastric cancer is still a matter of debate 39 and deserves further analyses. Unfortunately, the magic trial has not reported a rate of complete pathologic response.…”
Section: Discussionmentioning
confidence: 99%
“…Several small prospective studies have examined the use of induction ChT prior to preoperative CRT for potentially resectable gastric cancer [12-14]. Single institution experiences using either preoperative ChT and/or CRT have also been described [15-17], although the data examining a neoadjuvant approach in gastric cancer remains limited. Our institution has favored an approach of neoadjuvant CRT without induction ChT for patients primarily with locally advanced disease, prompting the present analysis of treatment-related toxicities and outcomes for this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several series have demonstrated that pathologic response to CRT is predictive of patient outcomes [12,13,15-17]. Three phase II trials from Ajani et al showed pCR rates ranging from 20% to 30% with the use of induction CT followed by concurrent CRT, [12-14] with associated improvements in OS and DFS in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been few articles evaluating patterns of failure in gastric cancer, particularly in patients who have received adjuvant chemoradiotherapy [7][8][9][10]. Dikken et al [9] reported their experience in 2010 and demonstrated a change in recurrence pattern, with distant failures outnumbering locoregional ones.…”
Section: Introductionmentioning
confidence: 99%